Adaptasi Alat Ukur Online Shopping Addiction Scale - Al-Ghiffari, Fuad Mohamad; Gani, Irfan Abdul; Mukminin, Ghinaya Ummul (Program Studi Psikologi Universitas Pendidikan Indonesia, 2022)
Abstract Online shopping addiction is a compulsive, excessive, and problematic tendency to shop via the internet that has consequences in economic, social, and emotional terms. This study aims to adapt the measuring tool The Online Shopping Addiction Scale from Zhao et al. (2017) into Indonesian. This research was conducted on 159 participants with an age range of 18-24 years, consisting of 35 men and 124 women. The measuring tool consists of 18 items that measure the six dimensions that have reliability 0.882 and the results of the calculation of the KMO MSA and the Bartlett's Test from SPSS version 27 show a statistical value of 0.855. Based on the calculation of the total variance explained, a value of 66.977 percent is obtained so that it can be concluded that this measurement tool is valid because it has a value above 50 percent. The value of the extraction calculation of this measurement tool produces 6 factors, the same as the initial blueprint, but with a different number and group of items.Keywords: addiction, online shopping scaleAbstrak Adiksi berbelanja online merupakan tendensi perilaku berbelanja melalui internet yang kompulsif, berlebihan, serta bermasalah yang menimbulkan konsekuensi dalam hal ekonomi, sosial, dan emosional. Penelitian ini bertujuan untuk mengadaptasi alat ukur The Online Shopping Addiction Scale dari Zhao et al. (2017) ke dalam bahasa Indonesia. Penelitian dilakukan kepada 159 partisipan dengan rentang usia 18-24 tahun, yang terdiri dari 35 orang laki-laki dan 124 orang perempuan. Alat ukur terdiri dari 18 item yang mengukur keenam dimensi yang memiliki reliabilitas 0,882 dan hasil perhitungan KMO MSA dan Bartlett's Test dari SPSS versi 27 menunjukkan nilai statistik sebesar 0,855. Berdasarkan perhitungan total variance explained didapatkan nilai sebesar 66,977 persen sehingga dapat disimpulkan bahwa alat ukur ini valid karena memiliki nilai di atas 50 persen. Nilai perhitungan ekstraksi pada alat ukur ini menghasilkan 6 faktor, sama dengan blueprint awal, tetapi dengan jumlah dan kelompok item yang berbeda. Kata kunci: adiksi, online shopping addiction scale